[Editorial] Critically examining international migration - Góis, P. (2022)
In this Editorial to the Special Issue, Góis, Oliveira and Gaspar offer a critical exploration of international migration, particularly in the Portuguese context. They challenge traditional perspectives, arguing that simplistic dichotomies are inadequate to understand the complexities of migration and integration. The authors delve into Portugal’s changing migration landscape, advocating for an appreciation of the diverse motivations and experiences of migrants. Emphasizing the need for inclusive, multicultural policies, the article highlights the importance of recognizing the heterogeneity within migrant communities. Central to the discussion is the interplay between knowledge, politics and migration policies. The authors analyse the influence of institutions in shaping public perception and policy formulation, stressing the need for a nuanced approach in migration studies. The challenges in measuring immigrant integration are addressed, with a focus on the multifaceted nature of integration within sociology. The article also tackles the complexities of racial categorization in the context of migration, emphasizing the fluidity of identities and calls for more inclusive approaches to understanding racial dynamics. Through its critical examination of migration phenomena, the article aims to enhance understanding and inform the development of more effective and inclusive migration policies.